(untitled) (Educação e Pesquisa, 2007)
The demand for evaluations of projects of virtual distance learning has required the use of concepts and methods that go beyond the strictly educational field, with emphasis on the multiplicity of theoretical frameworks and technical approaches employed in the assessment strategies of online learning. Despite the hegemony of quantitative methods in the evaluation of the technologies of information and communication, the use of qualitative methods in the assessment of virtual environments has increased throughout the last decades. The combination of qualitative-quantitative methods allows a better understanding of the phenomena underlying the use of technologies for online learning. Given that education in virtual environments relates to learning experiences that make use of hypermediatic resources within environments supported by an online communication technology, we have opted in the present article for focusing on topics associated to the evaluation of information and learning technologies in these environments, furthering the discussion concerning the methods relevant to the assessment both of the virtual learning environments and of the learning within this medium. This choice is due to the recognition of the specificities of the practices of distance learning, which stress the relationship between education and communication, made possible through the new information and communication technologies. It also recognizes the various roles, positive and negative, attributed to the information and communication technologies in education.